Comparative Analysis of Super-Kamiokande Solar Neutrino Measurements and Geological Survey of Israel Radon Decay Measurements - Sturrock, P. A.; Piatibratova, O.; Scholkmann, F. (Frontiers in Physics, 2021)
Analyses of neutrino measurements acquired by the Super-Kamiokande Neutrino Observatory (SK, in operation 1996 - 2001) and radon decay measurements acquired by the Geological Survey of Israel (GSI, in operation 2007 - 2017) yield strikingly similar detections of an oscillation with frequency (SK), (GSI); amplitude % (SK), % (GSI); and phase (SK), (GSI). This remarkably close correspondence supports the proposition that neutrinos may somehow influence nuclear decays. It is interesting to note that an oscillation at this frequency has also been reported by Alexeyev et al. (2016, 2018) in the decay of 214Po. The physical process responsible for this influence of neutrinos on nuclear peocesses is currently unknown. Related oscillations in GSI data at and suggest that these three oscillations are attributable to a solar core that rotates with a sidereal rotation rate of about an axis almost orthogonal to that of the convection zone. We briefly discuss possible implications of these results.